2015
DOI: 10.1097/gme.0000000000000249
|View full text |Cite
|
Sign up to set email alerts
|

Actigraphy-defined measures of sleep and movement across the menstrual cycle in midlife menstruating women

Abstract: Objective To evaluate patterns in actigraphy-defined sleep measures across the menstrual cycle, testing the hypothesis that sleep would be more disrupted in the premenstrual period, i.e. in the 14 days prior to menses. Methods A community-based, longitudinal study of wrist actigraphy-derived sleep measures was conducted with 163 women (58 African-American, 78 White, and 27 Chinese) of late reproductive age (mean=51.5, SD=2.0 years) from the Study of Women's Health Across the Nation (SWAN) Sleep Study. Daily … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
19
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(28 citation statements)
references
References 45 publications
(51 reference statements)
2
19
0
3
Order By: Relevance
“…These findings have also been seen in women of later reproductive age [32,131]. Interestingly, the predominant hormone during the luteal phase, progesterone, is a known GABA A receptor agonist [81] and exogenous administration increases sleep in post-menopausal women [25,94] and women in the early follicular phase [106].…”
Section: Reproductive Hormonal Milieu Influences Sleepmentioning
confidence: 50%
“…These findings have also been seen in women of later reproductive age [32,131]. Interestingly, the predominant hormone during the luteal phase, progesterone, is a known GABA A receptor agonist [81] and exogenous administration increases sleep in post-menopausal women [25,94] and women in the early follicular phase [106].…”
Section: Reproductive Hormonal Milieu Influences Sleepmentioning
confidence: 50%
“…These corresponding changes, however, were not found in PSG sleep 2224 . Recently, actigraphic sleep was examined in participants from the Study of Women’s Health Across the Nations (SWAN) and investigators found that among later reproductive-age women, sleep efficiency declines across the menstrual cycle with the most pronounced decline in the last week of the menstrual cycle 25 . Another recent study demonstrated that a steeper rate of rise in progesterone levels from follicular phase through mid-luteal phase was associated with greater PSG wake after sleep onset and sleep fragmentation in the late luteal phase 26 .…”
Section: The Menstrual Cycle and Menstrual Cycle Disordersmentioning
confidence: 99%
“…In addition, more women, both pre-and early perimenopausal, reported trouble sleeping in the late luteal and early follicular phases compared with other phases of the menstrual cycle (11). Recently additional SWAN data showed that actigraphy-derived sleep measures varied with menstrual phase in midlife women, with total sleep time and sleep efficiency declining gradually across the menstrual cycle, being lowest in the premenstrual (late-luteal) phase (12). It remains unknown how the polysomnogram (PSG) and sleep EEG are impacted by menstrual cycle phase in perimenopausal women.…”
mentioning
confidence: 96%
“…Most studies also show that sleep efficiency, wakefulness after sleep onset (WASO), and number of awakenings are similar across the menstrual cycle in young women. The most prominent effect of the menstrual cycle in young women is a marked increase in -electroencephalographic (EEG) activity (12)(13)(14)(15), presumed to reflect an increase in sleep spindles (brief bursts of ϳ12-15 Hz synchronous activity), in the luteal compared with the follicular phase (7)(8)(9), although only one small study has assessed menstrual cycle modulation of sleep spindle characteristics (10).…”
mentioning
confidence: 99%